From the Bulletin International des Sociétés de la Croix Rouge to the International Review of the Red Cross: The Great War as a revelator. (April 2018) - Becker, Annette
Abstract: During the Great War, the Bulletin International des Sociétés de la Croix Rouge covered the immense work of the International Committee of the Red Cross (ICRC) and the National Red Cross and Red Crescent Societies (National Societies). This article focuses on one particular angle of that work: the tensions and even contradictions between the ICRC's duty of neutrality and impartiality, on the one hand, and the national and sometimes nationalistic commitments of National Societies, which were naturally opposed to each other in wartime, on the other. While some of the Bulletin 's articles revealed real advances in thought on war and the protection of victims, others reflected the inertia caused by this fundamental contradiction.